SOMATOTYPOLOGICAL CHARACTERISTIC OF THE REPRESENTATIVES OF DIFFERENT AGE PERIODS AND ITS IMPORTANCE IN SPORTS ORIENTATION - N. S. Bakhareva; S. E. Baibakov; D. R. Yulmukhametov; E. K. Gordeeva; A. A. Bakhareva (Кубанский научный медицинский вестник)
Aim. The study was designed for the theoretical analysis of the somatotypological characteristics of people of the second childhood, adolescent, youthful and mature age periods and their importance for sports orientation.Materials and methods. In course of the theoretical analysis, the search was performed in Scopus, eLIBRARY and PubMed databases using the keywords “somatotype”, “morphometry”, “somatometry”.Results. The presented materials are considered from the ecological, geographical, ethnical and territorial perspectives that have a significant impact on the constitutional heterogeneity of the population. The features of the somatotypological characteristics of boys and girls participating in various sports are being specified. Concluding the analysis of the literature, it can be stated that in a number of studies, certain ratios of the main body types were observed in healthy individuals of various ethnical and territorial groups. However, upon closer acquaintance with this material, significant contradictions are revealed regarding the nature and the degree of manifestation of these shifts, and, in some cases, even mutually exclusive statements are made.Conclusion. In view of the above, it is possible to conclude that further systematic study of these issues is needed.